2022
DOI: 10.1021/acsnano.2c05110
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Synthesis of Multifunctional Apatite via the Laser-Induced Hydrothermal Process

Abstract: Synthetic biomaterials are used to overcome the limited quantity of human-derived biomaterials and to impart additional biofunctionality. Although numerous synthetic processes have been developed using various phases and methods, currently commonly used processes have some issues, such as a long process time and difficulties with extensive size control and high-concentration metal ion substitution to achieve additional functionality. Herein, we introduce a rapid synthesis method using a laser-induced hydrother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…The artificial manufacture of hydroxyapatite is mainly produced in the form of micron and nanometer particles [ 35 ]. However, many recent studies have shown that nanohydroxyapatite has better bone conductivity because its size is similar to natural hydroxyapatite found in bone [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The artificial manufacture of hydroxyapatite is mainly produced in the form of micron and nanometer particles [ 35 ]. However, many recent studies have shown that nanohydroxyapatite has better bone conductivity because its size is similar to natural hydroxyapatite found in bone [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…When processing Ti6Al4V titanium alloy using LISSC, it was observed in XRD and TEM tests that the crystallinity of HA was low. This is considered to be because as HA becomes nanoparticles, the surface energy increases, and as a result, more serum proteins are attached, and bone conductivity also increases [50]. In addition, when the HA layering amount was high, the number of serum proteins and osteocytes attached to the surface increased.…”
Section: Discussionmentioning
confidence: 99%
“…The laser processing of nanomaterials has garnered significant interest due to its precision in manipulating and modifying materials at the nanoscale. 78 This technique has found applications across various domains, including electronics, 79 bioelectronics, 80,81 energy, 82 and materials science. 83 The principal advantages of laser processing include its exceptional precision, which allows for the precise modification, cutting, and structuring of nanomaterials with minimal thermal impact on adjacent areas.…”
Section: Laser-assisted Fabrication Processes For Solar Water-splitti...mentioning
confidence: 99%